SARS-CoV-2 hijacks folate and one-carbon metabolism for viral replication - Yuchen Zhang (Nature Portfolio, 2021)
Viruses rely on host metabolism for replication. Here, the authors perform transcriptional and metabolomic analyses at 8 hours after SARS-CoV-2 infection and find that the virus alters host folate and one-carbon metabolism at a post-transcriptional level.